1988
DOI: 10.1126/science.242.4884.1403
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Low Temperatures and Biologic Diversity in Cretaceous High Latitudes of Australia

Abstract: A diverse terrestial biota inhabited polar latitudes during the Cretacous, 105 to 130 Ma (million years ago), along what is now the southeast coast of Australia This biota, from rocks in the Otway and Strzelecki groups, cnsisted of more than 150 taxa of vertebrates, invertebrates, and plants. Oxygen isotope ratios in diagenetic calcite suggest that mean annual temperatures were most likely less than 5 degrees C, and rings present in the fossil araucarian-podocarp-ginko woods indicate saonality. Southeastern Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…The distribution of polar dinosaurs is widespread and taxonomically variegated (Rich et al 1988, Nelms 1989, Hammer & Hickerson 1993, Molnar & Wiffen 1994, Slaughter et al 1994, Gangloff 1995, Case et al 2000, Fiorillo & Parrish 2004, Gangloff et al 2005see Rich et al 1997 for a review). Considerable taxonomic overlap is observable, at least at the generic level, between polar and more temperate latitudes.…”
Section: Migrationmentioning
confidence: 99%
See 3 more Smart Citations
“…The distribution of polar dinosaurs is widespread and taxonomically variegated (Rich et al 1988, Nelms 1989, Hammer & Hickerson 1993, Molnar & Wiffen 1994, Slaughter et al 1994, Gangloff 1995, Case et al 2000, Fiorillo & Parrish 2004, Gangloff et al 2005see Rich et al 1997 for a review). Considerable taxonomic overlap is observable, at least at the generic level, between polar and more temperate latitudes.…”
Section: Migrationmentioning
confidence: 99%
“…Rich et al (1988) described a flora dominated by ginkgoes, podocarps, and araucarian conifers. Isotopic (d 18 O) records indicate that mean annual palaeotemperatures were around 58C (Rich et al 1988, Gregory et al 1989, with seasonal freezing as evidenced by cryoturbation structures (Constantine et al 1998), although Morath & White (2004) have suggested that a marine influence may have had an ameliorating affect on the climate. As such, temperatures were markedly warmer at the poles then than they are today, allowing a flourishing dense polar vegetation that was not conducive to freedom of movement (i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Dinosaur localities of Early Cretaceous Victoria were formed at the most southerly paleolatitudes of any known dinosaur sites (>70°S; Rich et al, 1988), including those in Antarctica now . During the Cretaceous, Australia and Antarctica were conjoined.…”
Section: Comparison Of the Drift Paths Of Africa South America And mentioning
confidence: 99%